Conversation topics, benefits and challenges of heterosexual friendships as perceived by older adolescent from the University of the Philippines Diliman - Gamboa, Maria del Cielo Beltran (College of Home Economics, University of the Philippines Diliman, 2010)
Heterosexual friendships increase during the period of late adolescence, however, there have only been minimal studies done regarding this type of friendship. This prompted the researchers to focus on the nature of heterosexual friendships. The present study aimed to provide a rich description of the conversation topics, benefits, and challenges of heterosexual friendships as perceived by male adolescents and female adolescents. The study used a non-probability purposive sampling that yielded a total of 86 survey respondents, 43 males and 43 females, aged 18-21, who are currently in their 3rd to 5th year of college in the University of the Philippines Diliman. Respondents were asked to determine the conversation topics,benefits and challenges of their respective heterosexual friendships. Answers from the survey were organized by subtopic (a. conversation topics, b. benefits, and c. challenges) and the responses with similar ideas were merged together. The study generated a total of 38 conversation topics, 36 benefits, and 47 challenges of heterosexual friendships as perceived by male and female respondents. Answers garnering a frequency of at least 20% of the sample size were regarded as considerable answers and noted for discussion. Thirty individuals part of 15 friendship pairs proceeded to be interviewed. Data gathered from the interview s provided in-depth explanation for the conversation topis, benefits and challenges that emerged considerable in the surveys. Findings revealed that there are similiraties in the conversation topics, benefits and challenges of heterosexual friendships as perceived by male and female adolescents. However, it was also evident that there are conversation topics, benefits and challenges that are distinctly perceived by adolescent males and those distinctly perceived by adolescent females. The study provides insight on gender differences with regards to the social development of adolescents thus granting better understanding of the adolescent life stage. Future studies can employ a larger sample of respondents, use a more sophisticated statistical analysis, and can concentrate on more specific dimensions of heterosexual friendships.